2014
DOI: 10.1080/09168451.2014.910092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low molecular weight soybean peptide on mRNA and protein expression levels of differentiation markers in normal human epidermal keratinocytes

Abstract: Low molecular weight soybean peptide (LSP) was applied to normal human epidermal keratinocytes, and the results showed a significant increase in the gene expression levels of involucrin, transglutaminase, and profilaggrin. Filaggrin protein levels were also significantly higher. It is possible that LSP has an epidermal cell differentiation-promoting effect and may be able to regulate metabolism of the epidermis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…The induction of ichthyosis vulgaris and allergen response has been reportedly associated with loss-of-function mutations in the filaggrin gene, resulting in defective barrier functioning [28,30,31]. In 2014, Tokudone et al, reported that a low molecular weight peptide originating from soybean can modulate epidermal metabolism by enhancing the gene expression of involucrin and profilaggrinin in human epidermal keratinocytes [32]. Soybean trypsin inhibitor (STI) and Bowman-Birk protein inhibitor (BBI) were first isolated from soybean in the early 1940s.…”
Section: Soybean Peptidesmentioning
confidence: 99%
“…The induction of ichthyosis vulgaris and allergen response has been reportedly associated with loss-of-function mutations in the filaggrin gene, resulting in defective barrier functioning [28,30,31]. In 2014, Tokudone et al, reported that a low molecular weight peptide originating from soybean can modulate epidermal metabolism by enhancing the gene expression of involucrin and profilaggrinin in human epidermal keratinocytes [32]. Soybean trypsin inhibitor (STI) and Bowman-Birk protein inhibitor (BBI) were first isolated from soybean in the early 1940s.…”
Section: Soybean Peptidesmentioning
confidence: 99%
“…Some of these peptides exert numerous beneficial effects, such as antidiabetic, anticancer, hypotensive, anti-inflammatory, and radical scavenging effects, in various experimental models. Soybean peptides have an average molecular weight of approximately 3-10 kDa and high glutamic acid content [4]. Enzymes, bacteria, and types of soy protein affect the composition and production of peptides [5].…”
Section: Introductionmentioning
confidence: 99%